The Role of Scout Extracurriculars in Shaping The Character of Social Care - Aqodiah Aqodiah; Niswatun Hasanah; Humaira (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2023)
This research seeks to comprehend the implementation of Scout extracurricular activities in shaping social awareness in the era of globalization.  Employing a qualitative descriptive research method, the study draws primary data from students and the Scout Leader School Principal.  Data were collected through interviews and documentation, employing a creative source triangulation test for ensuring data validity. Following Miles and Huberman's process, the study encompasses data collection, reduction, presentation, and inference.  The findings reveal that scout extracurricular activities have the potential to cultivate social awareness among students, fostering empathy and a sense of ownership towards the nation and patriotism.  Notably, students' social awareness and character exhibit significant improvement over time with consistent participation in scout activities.  This research holds relevance for adoption by other schools in Indonesia, particularly in the context of extracurricular activities such as scouting.  Given the prevalence of scout groups in nearly all schools in Indonesia,  from primary to tertiary levels, the findings of this study can be broadly applied.